An intimate and contested relation - Alessandra, Lorini (Firenze University Press, 2006)
The essays in this book explore the political, social and cultural complexity of the relations between the United States and Cuba in the nineteenth and twentieth centuries. They address aspects ranging from the Cuban exiles who from the States forged the independence of their homeland, the profound transformation of Cuban society during the American military occupation of 1898-1902, the coalitions and the conflicts between North American and Cuban feminism, and between the Afro-American racial identity and the Cuban national identity. At the crux of this relationship is the American military intervention of 1898, perceived in Europe at the time as a "war between civilisations", and the legacy of the thought of José Martí.